Estudio comparativo del Paseo Procesional del Chagra y la influencia de la aculturización en la Ciudad de Machachi, Cantón Mejía, Provincia de Pichincha - Salazar Guamán, Luis Fernando (2017)
Ecuador is a country that has a large quantity and variety of culture in each of its provinces. Globalization is one of the factors for development and knowledge, however, it has also become an element for the damage of cultural practices. The present study has as initial point the Paseo Procesional del Chagra, it is celebrated every year in July. In order to obtain the first objective, a general diagnosis was made of the study "El Paseo Procesional del Chagra", where each of the characters participating in this walk were registered. In addition, using the methodology and related technique for this study resulted in 5 characters that are the most representative in this party. The second objective is defined by identifying important actors with a space of one generation in ages; As they are 90, 70 and 30 years old being the main actor the oldest. In order to facilitate the collection of real and accurate data, information is collected through collective memories, addressed to principal actors. The information is compiled by generation to determine the changes to Paseo Procesional del Chagra in this timeline. The phases of the Paseo Procesional del Chagra were defined and the generational changes could be observed; As a result variants were obtained that are determinant in the chacarera culture. In order to determine the third objective, a comparative analysis was carried out through which the information obtained was systematized and it was concluded that the influence of globalization has effectively changed the processes of the party confirming that the culture is dynamic and changing. Directly affects the essence of the Processional Walk of the Chagra.